Features of Government Lending To Agricultural Entities and Their Influence on Supply Chain Management Strategies - Iaroslav V.Petrunenko (International Journal of Supply Chain Management, 2019)
The article is devoted to the study of the influence of government lending to agricultural entities on the choice of the correct strategy of supply chain management in the production of products. We have defined the concept and features of government lending to agricultural entities. The current state of government lending to agricultural entities has been described. The main strategies of supply chain management have been analyzed. The economic indicators of the influence of government lending to agricultural entities and its influence on the choice of supply chain management strategy have been determined. As a result, the efficiency of public lending to agricultural entities has been made and proposals for improving the efficiency of supply chain management have been suggested.